Mangrove Warrior Cilik: Edukasi Teknik Pembibitan Mangrove Bersama Di SDN 053 Bengkulu Utara - Andre Dirmansah; Hami Buldani; Hanifah dwi Aprianti; Lisa Regyna Ardianingrum; Yeli Melzeta Dwi; Ari Anggoro (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
The mangrove ecosystem in Enggano Island, Bengkulu Province, plays a crucial ecological role in preventing coastal abrasion, absorbing carbon, and providing habitat for various coastal species. However, low public awareness especially among younger generations regarding mangrove conservation remains a significant challenge. The Mangrove Warrior Cilik program in Enggano Island aimed to foster environmental awareness from an early age through education and hands-on mangrove seedling activities. This program involved sixth-grade students from SDN 053 Bengkulu Utara using a participatory and educational approach. The results showed improved student understanding of mangrove functions, along with increased awareness and active involvement in environmental conservation. This program demonstrates that experiential-based education is effective in shaping students’ environmental concern and commitment to preserving coastal ecosystems.